IMPLEMENTASI KURIKULUM MERDEKA PENDIDIKAN AGAMA ISLAM DI MI PUDJI HARDJO PRAMBON DAN PROBLEMATIKANYA - Janah, Rina; Fitri, Agus Zaenal (Taklim : Jurnal Pendidikan Agama Islam, 2024)
AbstractThe independent curriculum is designed to create quality education in accordance with current developments, which provides freedom and peace for educational units in preparing the curriculum according to student needs. However, the implementation of the independent curriculum policy in madrasas is still relatively new, so further analysis is needed in its implementation. This research aims to determine the implementation of the PAI independent curriculum at MI Pudji Hardjo Prambon, teacher problems in implementing the independent curriculum, and teachers' efforts to overcome problems. This research uses qualitative methods with observation, interview and documentation techniques. The results of the research were that MI Pudji Hardjo Prambon implemented an independent curriculum in classes I and IV. Teacher problems in implementing the independent curriculum include difficulties in designing open modules, choosing learning methods and strategies, lack of learning media and lack of socialization and training about the independent curriculum from related parties. Strategies for overcoming problems include regular meetings with the Teacher Performance Group, utilizing learning media in the madrasa environment, attending training on implementing the independent curriculum, collaborating with madrasa stakeholders with parents and the community. Keywords: Independent Curriculum, Curriculum Implementation, Islamic Religious Education, Madrasas, Teacher ProblemsAbstrakKurikulum merdeka dirancang dalam mewujudkan pendidikan bermutu sesuai dengan perkembangan zaman, yang memberikan kebebasan dan fleksibilitas kepada satuan pendidikan dalam menyusun kurikulum sesuai dengan kebutuhan siswa. Namun, kebijakan implementasi kurikulum merdeka di madrasah masih terbilang baru, sehingga perlu analisis lebih lanjut dalam pelaksanaannya. Penelitian ini bertujuan untuk mengetahui implementasi kurikulum merdeka PAI di MI Pudji Hardjo Prambon, problematika guru dalam implementasi kurikulum merdeka, dan upaya guru dalam mengatasi problematika. Penelitian ini menggunakan metode kualitatif dengan teknik observasi, wawancara, dan dokumentasi. Hasil penelitian yaitu MI Pudji Hardjo Prambon menerapkan kurikulum merdeka pada kelas I dan IV. Problematika guru dalam implementasi kurikulum merdeka seperti kesulitan merancang modul ajar, pemilihan metode dan strategi pembelajaran, kurangnya media pembelajaran serta kurangnya sosialisasi dan pelatihan tentang kurikulum merdeka dari pihak terkait. Strategi dalam mengatasi problematika melalui pertemuan rutin dengan Kelompok Kinerja Guru, memanfaatkan media pembelajaran di lingkungan madrasah, mengikuti pelatihan implementasi kurikulum merdeka, melakukan kerjasama stakeholder madrasah dengan orang tua siswa dan masyarakat. Kata kunci : Kurikulum Merdeka, Implementasi Kurikulum, Pendidikan Agama Islam, Madrasah, Problematika Guru